2010
DOI: 10.1007/s12374-010-9130-y
|View full text |Cite
|
Sign up to set email alerts
|

The Pathway and Regulation of Salicylic Acid Biosynthesis in Probenazole-Treated Arabidopsis

Abstract: Probenazole (PBZ; 3-allyloxy-1,2-benzisothiazole-1,1-dioxide) is a highly effective chemical inducer of systemic-acquired resistance (SAR). It has been used widely to protect rice plants against the rice blast fungus Magnaporthe grisea. Previous studies have shown that PBZ induces SAR through enhanced accumulation of salicylic acid (SA). Plants synthesize SA by either a pathway that uses phenylalanine as substrate or another that involves isochorismate. To clarify how SA is produced in PBZ-treated Arabidopsis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Previously, we have shown that probenazole, an effective inducer of systemic acquired resistance, efficiently induces ICS1 expression in Arabidopsis (Yu et al, 2010). In the present study, we used the yeast one-hybrid (Y1H) system to screen for upstream direct regulators of ICS1, and identified TCP8, a transcription factor of the TEOSINTE BRANCHED1/CYCLOIDEA/PCF (TCP) family.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previously, we have shown that probenazole, an effective inducer of systemic acquired resistance, efficiently induces ICS1 expression in Arabidopsis (Yu et al, 2010). In the present study, we used the yeast one-hybrid (Y1H) system to screen for upstream direct regulators of ICS1, and identified TCP8, a transcription factor of the TEOSINTE BRANCHED1/CYCLOIDEA/PCF (TCP) family.…”
Section: Introductionmentioning
confidence: 92%
“…Free SA was then extracted and quantified from approximately 350 mg tissue per sample using HPLC analysis as previously described (Yu et al, 2010). Briefly, tissues were homogenized and sonicated twice in 3 ml of 100% methanol.…”
Section: Salicylic Acid Quantificationmentioning
confidence: 99%
“…Total contents of SA (the sum of free and conjugated SA) in tomato leaves were detected according to Jin Yu et al with some modification. 32 Harvested tomato leaf materials (∼1 g) were ground in liquid nitrogen and homogenized briefly in a mortar after addition of 3 mL methanol (90% v/v). After centrifugation for 15 min at 4 • C at × 12 000 g, the pellet was re-extracted with 3 mL 100% methanol.…”
Section: Quantification Of Salicylic Acid (Sa)mentioning
confidence: 99%
“…Plants synthesize SA via either a pathway that uses phenylalanine as the substrate or one that involves isochorismate (ICS). The route has phenylalanine ammonia lyase (PAL) and chorismate mutase1 (CM1) as catalytic enzymes, and BA2H hydroxylates benzoic acid to SA at the final step . Another route has isochorismate synthase (ICS1) and PBS3 as key factors .…”
Section: Resultsmentioning
confidence: 99%
“…The route has phenylalanine ammonia lyase (PAL) and chorismate mutase1 (CM1) as catalytic enzymes, and BA2H hydroxylates benzoic acid to SA at the final step. 31 Another route has isochorismate synthase (ICS1) and PBS3 as key factors. [32][33][34] Transcript levels of PAL and CM1 involved in the PAL route increased markedly by 6.778-and 5.246-fold, respectively.…”
Section: Determinations Of Sa Biosynthesis-related Genes and Enzymementioning
confidence: 99%